The recovery of the traditional vineyards of Santa Maria Island (Azores Portugal): preliminary results of stakeholders’views - Mesquita, Bárbara (2022)
The vineyards of the Santa Maria Island, Azores, have for centuries been planted in terraces divided into plots (corrals - currais) and sustained by dry stone walls. These vineyards are mostly located at the cliffs of the bays. The cultivation dates back to the settlement and the techniques used are similar to other Azorean islands. The plots have been partly abandoned causing the ruining of the walls and the growing of weeds. In 2018, a project for the recovery gathered the Regional and Local Government, the University of Azores and a company. Acknowledging the value of these cultural landscapes as patrimony, the main aim is the recovery for its traditional use: wine production. Involvement of the stakeholders is a pre-condition for recovering a cultural landscape the coastal environment of a small island. The goal of this study is therefore to collect broad views on the purpose(s) of the recovery process: s guidelines of the policies and programs. Trends on viticulture and wine production after-Phylloxera times were identified in the literature on local and regional history. The objective of these preliminary results is to improve further research3.The contents of the meetings and the literature showed a comprehensive approach on the difficulties and possibilities of the recovery of these landscapes. The information points out ways which go beyond the existing policies and activities. The wine production along with the granting of a formal status of patrimony is the key feature. Nevertheless for achieving resilience the recovery actions can be better aligned with the views of the stakeholders and the historical process. It seems worth to take into consideration the feasibility of other uses for the plots: some already into practice (e.g. traditional grapes that do not fulfill commercial requirements) and some new (e.g. vineyards as part of the walking trails). Any actions taken should respect a cultural landscape located on a coastal environment.